Speed Up, Size Down: How Animated Movement Speed in Product Videos Influences Size Assessment and Product Evaluation. (September 2020) - Jia, He (Michael); Kim, B. Kyu; Ge, Lin
Digital ads often display video content in which immobile products are presented as if they are moving spontaneously. Six studies demonstrate a speed-based scaling effect, such that consumers estimate the size of an immobile product to be smaller when it is animated to move faster in videos, due to the inverse size–speed association they have learned from the domain of animate agents (e.g., animals, humans). Supporting a cross-domain knowledge transfer model of learned size–speed association, this speed-based scaling effect is (1) reduced when consumers perceive a product's movement pattern as less similar to animate agents' movement patterns, (2) reversed when a positive size–speed association in the base domain of animate agents is made accessible, (3) attenuated for consumers who have more knowledge about the target product domain, and (4) mitigated when explicit product size information is highlighted. Furthermore, by decreasing assessed product size, fast animated movement speed can either positively or negatively influence willingness to pay, depending on consumers' size preferences.